Effectiveness of video assisted teaching program for caregivers on gross motor outcome among children with cerebral palsy undergoing hyperbaric oxygen therapy: A quasi-experimental study - Rania Ebrahim Abd-Elzaher; Ebtisam Mohamed Abd-El-Aal; Amina Abd-Elrazek mahmoud; Basma Mohamed Abd-Elrahman (Scientific Reports)
Abstract Caregivers play a crucial role in the care of children with cerebral palsy, and their practices greatly influence the development of gross motor skills. A quasi-experimental research design was utilized in the study. This study was conducted in the Hyperbaric Oxygen Therapy Unit at Nasser Institute for Research and Treatment in Cairo Governorate, Egypt. A purposive sample of 76 caregivers and their children with cerebral palsy (age 3–12 years, gross motor level I–III) were assigned to study and control groups. The study group underwent hyperbaric oxygen therapy treatment and received video assisted teaching program for about eight months. Tool I: An interviewing questionnaire comprised of two parts: caregivers- sociodemographic characteristics and children’s personal characteristics and medical history. Tool II: Caregiver Priorities & Child Health Index of Life with Disability to evaluate caregivers practices. Tool III: The Gross Motor Function Measure-88 is used to evaluate changes in the gross motor functions of children with cerebral palsy. The findings revealed that 71.1% and 65.8% of the study and control groups of caregivers were mothers with mean ages of 33.03 ± 4.750 and 32.42 ± 5.006 years, respectively. Before the implementation of the video-assisted teaching program, 34.2% of the children in both the study and control groups exhibited a total gross motor level I. After the program, this percentage increased to 84.2%. The analysis indicated a highly significant positive correlation between the total practices of the studied caregivers and the gross motor skills of their children with cerebral palsy following the implementation of the program. The video-assisted teaching program significantly enhanced the studied caregivers practices regarding care of their children with cerebral palsy, which positively affected gross motor skills among children with cerebral palsy of studied caregivers.